(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article examines the formation of the Kyrgyz-Tajik state border in the post-1990s period and the challenges associated with its resolution. The study analyzes several key factors that have influenced this process. The authors focus on issues of border delimitation and demarcation, the intensification of interethnic tensions in border villages, the use of water and land resources, and the problem of enclaves. Special attention is paid to how demographic pressures have contributed to the escalation of border disputes. The article emphasizes that resolving these issues is only possible through bilateral cooperation and dialogue.